2016
DOI: 10.3382/ps/pew146
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic analysis of causal relationships among feather pecking, feather eating, and general locomotor activity in laying hens using structural equation models

Abstract: The objective of this research was to analyze the relationship between feather pecking (FP) and feather eating (FE) as well as general locomotor activity (GLA) using structural equation models, which allow that one trait can be treated as an explanatory variable of another trait. This provides an opportunity to infer putative causal links among the traits. For the analysis, 897 F2-hens set up from 2 lines divergently selected for high and low FP were available. The FP observations were Box-Cox transformed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The occurrence of EFP birds may also be the result of the co-occurrence of SFP with other facilitating behaviors. Chickens from an HFP line were found to have significantly higher locomotor activity compared with chickens from an LFP (Kjaer, 2009;Lutz et al, 2016). Other behaviors, such as those involved in aggression (Bessei et al, 2013;Bennewitz et al, 2014), exploration (de Haas et al, 2010Brunberg et al, 2011) and fear Boegelein et al, 2014, Grams et al, 2015b have been reported to be associated with feather pecking and may have a complementary effect on this behavior.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of EFP birds may also be the result of the co-occurrence of SFP with other facilitating behaviors. Chickens from an HFP line were found to have significantly higher locomotor activity compared with chickens from an LFP (Kjaer, 2009;Lutz et al, 2016). Other behaviors, such as those involved in aggression (Bessei et al, 2013;Bennewitz et al, 2014), exploration (de Haas et al, 2010Brunberg et al, 2011) and fear Boegelein et al, 2014, Grams et al, 2015b have been reported to be associated with feather pecking and may have a complementary effect on this behavior.…”
Section: Discussionmentioning
confidence: 98%
“…So far, the majority of studies have applied research goals, while only few are categorized as oriented basic [17] or use-inspired basic research [18]. Despite the large body of research, the causes of feather pecking remain largely unknown [19]. Questions concerning the adaptive capacity of chickens, their behavioral repertoire and needs, and indices of negative and positive welfare states, would greatly benefit from basic research approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This skew suggests that the focus on a practical solution may have resulted in fundamental questions regarding feather pecking to remain unanswered and we consequently find ourselves with incomplete information on the causes of feather pecking. Despite extensive research efforts over the past few decades, the causes of feather pecking remain largely unknown [19]. Additionally, the focus understandably has mainly been on the welfare of the victims of feather pecking and solutions to improve their situation.…”
Section: Introductionmentioning
confidence: 99%
“…where y i is the number of bpb of each hen i and y ti is the transformed observation. The power parameter −0.2 was used according to Lutz et al [20] and Su et al [21] showing the best fit for feather pecking data.…”
Section: Experimental Design Data Collection and Editingmentioning
confidence: 99%